The Process of Decolonization on Islamic Law in Indonesia: A Historical Perspective - Sulasman, Sulasman (TAWARIKH, 2017)
ABSTRACT: The process of decolonization on Islamic law in Indonesia had a long history, namely from the Islamic kingdoms period, Ducth colonial government, to post-colonial period. This paper aimed at describing and explaining how the process of decolonization on history of Islamic law in Indonesia was. The historical method was employed to account for the facts of history. Based on the facts of history, the process of decolonization on Islamic law in Indonesia coincided with the development of Islam in Indonesia. The application of the Islamic law in Indonesia could not be separated from the roles of Islamic kingdoms in spreading out the teachings of Islam. The arrival of the Dutch colonial has predisposed the application of the Islamic law in Indonesia. The Dutch colonial government applied the theory of âReceptio in Complexuâ and the theory of âReceptieâ in the Islamic law in Indonesia. Both of these theories gave a very strong influence in the Dutch legal system in Indonesia. The Proclamation of Indonesian Independence was the starting point of the struggle for legal structure changes by performing the decolonization of law, including Islamic law decolonization through the emergence of the âReceptie Exitâ theory. This theory attempted to waive the Islamic law from the influence of decolonization and to direct that the Islamic law in Indonesia was based on Pancasila and the Constitution of 1945. This decolonization was designated by the emergence of Islamic law in the perspective of Indonesianness in the form of the Compilation of Islamic Law in Indonesia.KEY WORDS: Decolonization Process; Islamic Law; National Law System; Pancasila; Indonesia.About the Author: Prof. Dr. Haji Sulasman is a Lecturer at the Department of Islamic Civilization, Faculty of Adab and Humanities UIN SGD (State Islamic University, Sunan Gunung Djati) Bandung, Jalan A.H. Nasution No.105 Cipadung, Bandung 40614, West Java, Indonesia. For academic interests, the author is able to be contacted via e-mail at: sulasman@uinsgd.ac.idHow to cite this article? Sulasman. (2017). âThe Process of Decolonization on Islamic Law in Indonesia: A Historical Perspectiveâ in TAWARIKH: International Journal for Historical Studies, Vol.8(2) April, pp.131-142. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980.Chronicle of the article: Accepted (March 2, 2017); Revised (April 2, 2017); and Published (April 28, 2017).